2022
DOI: 10.1155/2022/8063651
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Albumin- and Bilirubin-Based Biomarkers in Glaucoma: A Retrospective Case-Control Study

Abstract: Glaucoma is the second leading cause of global blindness. The etiology of glaucoma is complicated. In addition to elevated intraocular pressure (IOP), several other mechanisms have been implicated in pathogenesis, such as oxidative stress and systemic inflammation. Serum albumin (ALB) and bilirubin (BIL) have been reported to have potent antioxidant properties and contribute to maintain redox homeostasis in various diseases. However, associations between these parameters and glaucoma remain mostly unknown. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…A recent study of 70 POAG patients found significantly lower TBIL levels than in the controls [ 15 ], which is contrary to the findings of our study. Potential reasons may be the following: first, differences in sample size (70 vs. 198) may result in inconsistent results; second, our study conducted gender subgroup analyses and found that TBIL levels were significantly correlated with POAG in the male subgroup but not in the female subgroup; mixed male and female analyses may also yield inconsistent conclusions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A recent study of 70 POAG patients found significantly lower TBIL levels than in the controls [ 15 ], which is contrary to the findings of our study. Potential reasons may be the following: first, differences in sample size (70 vs. 198) may result in inconsistent results; second, our study conducted gender subgroup analyses and found that TBIL levels were significantly correlated with POAG in the male subgroup but not in the female subgroup; mixed male and female analyses may also yield inconsistent conclusions.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, we hypothesized that bilirubin, an oxidative and cytotoxic stress biomarker, plays a vital role in the physiological and pathological conditions of glaucoma. However, only a few previous researches have been conducted on the association between bilirubin levels and POAG, and they have been limited by their sample sizes [ 15 ]. To investigate the connection between bilirubin and POAG, we did a large sample, cross-sectional, case-control investigation in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating CD4 + T cell activation status was examined in GL-cohort #1 and functional subsets of CD4 + T cells were examined in GL-cohort #2. As previously reported [ 13 , 14 ], the diagnosis of glaucoma was established by skilled ophthalmologists based on thorough ophthalmic examinations, considering factors such as age, family history, and clinical manifestations indicative of glaucomatous pathology. A comprehensive set of ophthalmic assessments was conducted, including evaluations of the anterior chamber angle, IOP measured on multiple occasions (with resulting averages recorded), cup-to-disk ratio, visual field loss, and retinal nerve fiber layer (RNFL) thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of the peripheral immune system has emerged as a critical factor in the etiology of glaucoma [ 7 11 ]. Our group, alongside others, has provided evidence implicating both innate and adaptive immune components [ 10 , 12 14 ], with considerable focus on CD4 + T cells in the past two decades [ 12 , 15 18 ]. In experimental glaucoma models, including inducible and genetic mouse models, increased infiltration of CD4 + T cells into the retina has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…In the CNS, stress such as ischemia-reperfusion injury can induce endogenous inflammatory factors such as damage-associated molecular patterns (DAMPs) and result in systemic inflammation and activation of immune cells. Similarly, EIOP stress could cause an influx of retina-derived DAMPs into the circulation, leading to a low-grade systemic inflammation (31,32) and up-regulation of proinflammatory cytokines (33)(34)(35), which can exaggerate T cell activation. In our study, we showed that activated and guteducated β7 + CD4 + T cells were able to induce MAdCAM-1 expression on the endothelial cells of glaucomatous retina and eventually led to neuroinflammation.…”
Section: Fig 7 β7 + Cd4 + T Cells Induce Retinal Vessel Expression Of...mentioning
confidence: 99%